Has Modern Retailing in India Influenced the Consumption Expenditure Behavior of Urban Socioeconomic Classes? - Banerjee, Debjani; Shivani, Shradha (Indian Journal of Marketing, 2015)
The retail industry of India is estimated to be valued at 470 billion. The modern trade retail occupies 8% share of the business. It was projected to reach US 574 billion by 2015. The organized retail market is estimated to grow at a CAGR of 18.8%, and increase its expansion to 20% of the retail share by 2020. The global retailers are finding India to be an attractive potential destination for their businesses. The expansion of organized retail in different formats has created ample opportunities and has brought a sea change in consumer buying behavior among the various socioeconomic classes in urban India. Modern retail focuses on various non price aspects of human preferences towards consumption behavior like- dietary diversity, convenience, quality and brand, which has implications for food demand. Again, the growing supply chain efficiencies that have reduced real food prices over time have facilitated in boosting consumer demand by relatively expanding the budget line. India, unlike any other nation, has diversity in terms of geographical spread and cultural aspects. The shift of retail towards the organized format has not affected consumption behavior in every sector uniformly. This paper focused upon identifying the impact of organized retail outlets on consumption behavior towards wet food, grocery, and apparel. The paper attempted to explore the organized retail industry and evaluated the extent of its impact on changing consumption expenditure in urban India based on a data set of 850 sample respondents spread across different places of Mumbai, Navi Mumbai, Thane, and Kalyan from different socioeconomic classes.